A IMPLEMENTASI LEARNIG DENGAN TECHNOLOGY SYSTEM ARCHITECTURE PADA MTS AL-ITTIHADIYAH: Learning Technology System Architecture - Yusup Achmad Achmad; Sofa Sofiana (CV. Multi Kreasi Media, 2022)
− In the education aspect, online media technology can provide many advantages and conveniences in the world of education so that it can save time and effort. MTS Al-Ittihadiyah is a private school that specializes in teaching methods by promoting Islam in all aspects of teaching and learning activities. This school does not yet have a system to facilitate teachers and students in teaching and learning activities, and there is no system that is integrated with computers to manage materials managed by the school and teachers. The development of an online learning media system carried out by researchers using the Learning Technology System Architecture (LTSA) method. By using the codeigniter framework and MySQL as the database, while for the design the researcher uses an object-based method with UML (Unifield Modeling Language) tools. Based on the problem analysis, the results obtained are learning media that can be accessed by admins, teachers and students. Admin can manage materials, manage teacher data and student data and supervise the online learning process carried out by teachers and students. Teachers can manage and manage materials, assignments, discussion forums and student grades online.